Factors Associated With Work Fatigue In Employees Of Computer Users At Pt. Glori Global Success Batam in 2022: Faktor - Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Karyawan Pengguna Komputer Di Pt. Glori Global Sukses Batam Tahun 2022 - Ningsi Aprianti; Winda Septiani; Zulmeliza Rasyid; Endang Purnawati Rahayu (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Work fatigue is a condition experienced by everyone which is characterized by decreased strength to carry out an activity.Work fatigue can also be interpreted as a condition of weakening endurance, activities, and motivation when completing a job. In addition, tedious work tasks and long working hours will be able to increase fatigue in these workers. The purpose of this study was to determine the Factors Associated with Work Fatigue on Computer User Employees at PT Glori Global Sukses Batam. The variables of this research thesis include working time, work attitude and workload. This type of research was conducted with quantitative methods with cross sectional design with total sampling technique and obtained data by distributing questionnaires. With a sample of 61 people, this research was conducted in May – June 2022 at PT. Glori Global Success Batam. The results of the study can be concluded that there is a relationship between working time (p value = 0.014), work attitude (p value = 0.003), workload (p value = 0.033) with work fatigue in computer users, work for about 5-10 minutes such as light exercise, standing in place to stretch the body mucles to the accompaniment of music so that workers can be more comfortable and relaxed at work.